Optimal scheduling of distribution systems considering multiple downward energy hubs and demand response programs - Bostan, Alireza; Nazar, Mehrdad Setayesh; Shafie-khah, Miadreza; Catalão, João P. S. (Elsevier, 2020)
This paper presents a two-level optimization problem for optimal day-ahead scheduling of an active distribution system that utilizes renewable energy sources, distributed generation units, electric vehicles, and energy storage units and sells its surplus electricity to the upward electricity market. The active distribution system transacts electricity with multiple downward energy hubs that are equipped with combined cooling, heating, and power facilities. Each energy hub operator optimizes its day-ahead scheduling problem and submits its bid/offer to the upward distribution system operator. Afterwards, the distribution system operator explores the energy hub’s bids/offers and optimizes the scheduling of its system energy resources for the day-ahead market. Further, he/she utilizes a demand response program alternative such as time-of-use and direct load control programs for downward energy hubs. In order to demonstrate the preference of the proposed method, the standard IEEE 33-bus test system is used to model the distribution system, and multiple energy hubs are used to model the energy hubs system. The proposed method increases the energy hubs electricity selling benefit about 185% with respect to the base case value; meanwhile, it reduces the distribution system operational costs about 82.2% with respect to the corresponding base case value.
Keywords: Combined Cooling Heating and Power (CCHP); Mixed integer linear programming (MILP); Active distribution system; Demand response program; Energy hub; fi=Sähkötekniikka|en=Electrical Engineering|